Investigating the evolution of landscape patterns in historical subdeltas and coastal wetlands in the Yellow River Delta over the last 30 years: A geo-informatics approach - Zhan, Chao; Wang, Qing; Cheng, Shanshan; Zeng, Lin; Yu, Jiankui; Dong, Cheng; Yu, Xiang (Frontiers in Marine Science, 2023)
Historically, the river course and coastline of the Yellow River Delta changed frequently, and many studies focused on these change trends and their driving forces. Few studies have explored the influence of historical river channels and historical coastlines on the response of modern landscape patterns. This study examines the impact of channel migration and coastline evolution on the modern landscape pattern of historical subdeltas and coastal wetlands, utilizing a combination of Geo-informatics and Remote Sensing images in 1989, 1998, 2009, and 2016. The results showed that: (1) Subdeltaic landscapes changed from 1998 to 2016, with slight changes in most landscape types in the Ancient Qing Shui Course Subdelta (AQSD), an increase in building sites by 17% in the Zhimai Course Subdelta (ZMSD), a decrease in the proportion of Phragmites/cogongrass communities by 15.8% in the Diao Kou Course Subdelta (DKSD), and domination by natural landscapes in the Modern Qing Shui Course Subdelta (MQSD). (2) Coastal wetlands also experienced changes, with an increase in cultivated land to 60% in the coastal wetlands of CWI, a decline in natural landscapes, and an increase in artificial landscapes in the coastal wetlands of CWII and CWIII, and domination by natural landscapes but an increase in salt fields and culture ponds by 3.45% in the coastal wetlands of CWIV. (3) Channel migration and coastline evolution influenced the direction of landscape succession, causing the landscape-type centroids in the entire delta to move eastward or northward. (4) Throughout the delta, the human tendency to live by rivers was observed. This was due to the availability of freshwater from these rivers, which led to the expansion of inhabited areas and man-made water bodies along the river banks. Channel migration and coastline evolution aggravated the salinization of coastal wetlands and promoted the salt industry and aquaculture in some estuaries of the Yellow River. In general, human activities play a dominant role in shaping the landscape pattern in the Yellow River Delta, but they were largely restricted to historical channel migration and historical coastline evolution.